Design and evaluation of a computer-assisted instruction material in heat and thermodynamics - Avila, Arlene M. (Animo Repository, 1998)
This study designs and evaluates a computer-assisted instruction (CAI) material in Heat and Thermodynamics. Specifically, the study determines the responses of the student teachers and teachers on the developed CAI based on its objectives, quality of content, instructional quality, technical quality, significance and effectiveness. It does not, however, rate the developed CAI in heat and thermodynamics. The study also determines if the developed CAI in Heat and Thermodynamics can be an alternative teaching tool in teaching heat and thermodynamics .The developed CAI was a tutorial type of program that included lessons in Heat and Thermodynamics for the high school level. The development phase involved the collection and review of related resources, selection of the authoring program, design of the CAI program, development of the program, and evaluation of the developed CAI. Available CAI materials in science, mathematics and English were reviewed to facilitate in designing the program. The authoring program was selected giving considerations to the program's portability, licensing agreement, and capability for graphics and animation. The design process involved several tasks such as formulating and sequencing of objectives, categorizing the lessons and activities, designing the presentation and interaction screen, formulating summary tests, developing a prototype, and designing the computer-managed instruction. The design scripts were converted to computer screens using Authorware (Ver. 3.5). Thirteen fourth-year BSPT student teachers, two physics teachers of Philippine Normal University, and two experts in educational technology evaluated the CAI. The evaluators evaluated the material based on objectives, quality of content, instructional quality, technical quality, significance and effectiveness. From a scale of one (strongly disagree) to five (strongly agree), the student teachers gave a rating of 4.46 on objectives 4.52-quality of content 4.45- instructional quality 4.52-technical quality 4.44-significance and 4.31 on effectiveness. The student's mean response on the CAI was 4.45.The teachers had a mean of 4.63, 4.67, and 4.43 on objectives, quality of content, and instructional quality, respectively. Technical quality, significance and effectiveness had a mean of 4.36, 4.44, and 4.35, respectively. The mean of the teachers' evaluation was 4.48.The teachers gave a more positive response (mean = 4.48, s = 0.571) on the items in the evaluation compared to the student teachers' response (mean = 4.45, s = 0.514). The teachers agreed more strongly than the student teachers on objectives, quality of content, and effectiveness. The student teachers gave a more positive response than the teachers on instructional quality, and technical quality. The student teachers and the teachers gave the same response on significance as indicated by a mean of 4.44.From responses given by the evaluators on the CAI material, it was concluded that the CAI material can be used as an alternative teaching tool in Heat and Thermodynamics.